An Adenovirus-Based Recombinant Herpes Simplex Virus 2 (HSV-2) Therapeutic Vaccine Is Highly Protective against Acute and Recurrent HSV-2 Disease in a Guinea Pig Model - Mingming Wan; Xiao Yang; Jie Sun; Xue Ding; Zhijun Chen; Weiheng Su; Linjun Cai; Ali Hou; Bo Sun; Feng Gao; Chunlai Jiang; Yan Zhou (Viruses, 2023)
Genital herpes (GH) has become one of the most common sexually transmitted diseases worldwide, and it is spreading rapidly in developing countries. Approximately 90% of GH cases are caused by HSV-2. Therapeutic HSV-2 vaccines are intended for people already infected with HSV-2 with the goal of reducing clinical recurrences and recurrent virus shedding. In our previous work, we evaluated recombinant adenovirus-based vaccines, including rAd-gD2ΔUL25, rAd-ΔUL25, and rAd-gD2, for their potency as prophylactic vaccines. In this study, we evaluated these three vaccines as therapeutic vaccines against acute and recurrent diseases in intravaginal challenged guinea pigs. Compared with the control groups, the recombinant vaccine rAd-gD2ΔUL25 induced a higher titer of the binding antibody, and rAd-gD2 + rAd-ΔUL25 induced a higher titer of the neutralizing antibody. Both rAd-gD2ΔUL25 and rAd-gD2 + rAd-ΔUL25 vaccines significantly enhanced the survival rate by 50% compared to rAd-gD2 and reduced viral replication in the genital tract and recurrent genital skin disease. Our findings provide a new perspective for HSV-2 therapeutic vaccine research and provide a new technique to curtail the increasing spread of HSV-2.